IMPACT OF COLD DRINKS ON UNIVERSITY LEVEL STUDENTS: A CASE STUDY OF UNIVERSITY OF MALAKAND PAKISTAN - Fazal Shakoor; Muhammad Ismail; Sehran Hassan; Nabeel Khan; Anwar Ali; Nadeem Khan; Sajid Shah; Kifayat Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the effects of cold drink consumption on the academic performance and health of university students. Utilizing a quantitative research approach, data was collected on the frequency and brand of cold drinks consumed and analyzed for its association with students’ health outcomes and academic achievements. The findings indicate a significant relationship between the quantity of cold drinks consumed and both health and academic performance, suggesting that higher consumption correlates with poorer outcomes in these areas. Additionally, the specific brand of cold drinks was found to significantly affect health and academic performance, highlighting the importance of ingredient variations among different brands. Conversely, the mere usage of cold drinks, irrespective of quantity or brand, showed an insignificant association with health and academic outcomes. These results underscore the need for targeted educational programs, healthier beverage alternatives, and campus policies to mitigate the negative impacts of cold drink consumption. The study concludes with recommendations for universities to promote healthier lifestyle choices among students, ultimately aiming to enhance their well-being and academic success.